Productivity of lesser yam [Dioscorea esculenta (Lour.) Burkill] as affected by seed tuber size and spacing - Sebastian, Anasooya; Prameela, P.; Menon, Meera V. (Journal of Tropical Agriculture, 2020)
A field experiment was conducted to study the effect of seed tuber size and spacing on the productivity of lesser yam during May to December 2018 at KAU campus, Vellanikkara, Thrissur. Tubers weighing 50 g, 100 g and 150 g were planted at spacings of 50 cm x 50 cm (high density), 75 cm x 50 cm (medium density) and 75 cm x 75 cm (low density: recommended spacing), adopting randomized block design with nine treatments. Significant effect of large seed tubers contributing to higher total dry matter accumulation per plant was observed at 180 days after planting (DAP), while spacing had no significant effect. Leaf area index was higher for vines from large seed tubers and closer spacing at all growth stages except towards senescence. The highest tuber yield per plant was realized from 150 g seed tubers (1270 g/plant), followed by 100 g (1053 g/plant) and 50 g seed tubers (929 g/plant). Wider spacing showed significantly higher per plant yield (1217 g), compared to medium (1062 g) and closer spacing (972 g). However significantly higher productivity of 44.20 t/ha was realized with 150 g tubers under high density. The next best and comparable productivity was realized with 100 g (37.09 t/ha) and 50 g (35.36 t/ha) tubers, planted at closer spacing of 50 cm x 50 cm, and 150 g tuber at a spacing of 75 cm x 50 cm (31.80 t/ha)